Pengaruh Pengembangan Sumber Daya Manusia Dan Motivasi Kerja Terhadap Kinerja Anggota Kepolisian Pada Satuan Sabhara Di Polres Karawang - Maesaroh, Siti; Tuhagana, Aji; Khalida, Laras Ratu (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research was conducted on members of the Police at the Karawang Police Sabhara Unit with the aim of knowing and analyzing how to develop human resources, work motivation and performance as well as to find out and analyze whether there is a partial or simultaneous influence between HR development and work motivation on the performance of police members in the Sabhara unit Karawang Police. The research method used in this research is descriptive and verification method. The sample used was 94 members with the simple random sampling method. The data analysis technique used is the scale range analysis technique and multiple linear regression analysis. The results of the descriptive analysis show that HR development and member performance are in the agree category while work motivation is in the moderately agree category. As for the results of the verification analysis, it was found that the development of human resources and work motivation partially and simultaneously had a significant effect on the performance of members of the Police at the Karawang Police Sabhara Unit.